Building interactive data visualizations with D3.js - Simoes, Alex; Westbay, Michael; Safari eBooks ([Place of publication not identified] : Packt Publishing, 2015)
"D3.js is a JavaScript library that enables data to drive interactive graphical forms and makes complex data analysis easier. Nowadays, big data, data deluge, and analytics are all trending buzzwords, so how does D3.js make sense of all this data? Simply by using visualizations and defining rules for dynamic graphics engines, which allows users to gain rich insights from large and complex datasets. Building Interactive Data Visualization with D3.js showcases the D3 JavaScript library built specifically for the use of driving visual elements with data. This video course will walk you through the basics of the library by showing its core components and methodologies. By following along with the examples in this video you'll become proficient at creating dynamic visualizations driven by user interactivity. This course starts with the very basics of frontend web development showing the challenges of incorporating dynamic graphics without using D3. Users learn to combine data with visual elements on the page to create informative visualizations. By the end of this section, viewers will be comfortable with using the D3 library to create their own custom concept of data-driven visualizations. We'll see how to use real datasets via APIs to create custom visualizations. By leveraging the interactive nature of web programming we'll look at how to incorporate user input to add interactivity to our visualization. We'll start with basic scatter plots and slowly build upon this foundation to create more complicated forms of dynamic data visualizations. Eventually we'll end the video course by walking through the process of creating a completely novel form of visualization merging concepts of both a scatter plot and a geographic map. Building Interactive Data Visualization with D3.js provides one with the foundation to continue on their journey of creating novel and highly impactful data visualizations."--Resource description page.
Title from title screen (viewed October 14, 2015).
Presenters, Alex Simoes, Michael Westbay.
Date of publication from resource description page.
Keywords: JavaScript (Computer program language); Information visualization; Big data; Electronic books